Study on Students’ Satisfaction of Covid-19 Sop Implementation in Uthm Pagoh Campus During Post Pandemic Era - Muhammad Fahmi bin Ahmad Fauzi, (Progress in Engineering Application and Technology, 2023)
The emergence of COVID-19 pandemic has sparked massive impact towards the whole world, with every industry could not prevent themselves from being affected. The implementation of new normal with strict guidelines has caused people to shift towards an unprecedented situation, where human interaction becomes limited because social distancing needs to be applied everywhere. Facilities that are available also needs to be subjected towards change, where the usage of them needs to adapt with the new and stricter guidelines to prevent the spread of this infectious virus. After higher educational institute such as universities started to reopen and welcome students back to respective campuses, the guidelines that newly implemented meaning students must follow them strictly and comply to the guidelines that the university has decided on. Their perception on the operational facilities usage is in question for this research, and a quantitative method with the use of a questionnaire has been conducted to achieve the results of this study. After a series of data collecting and analyzing, it can be said that this research has concluded positive perceptions from students involved in this study about their experience in the campus after the pandemic. However, improvements also cannot be ruled out for a better user experience in the future, in case our country has to face the same situation again.